2004
DOI: 10.1079/bjn20041175
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the bioavailability of the provitamin A carotenoid, β-carotene, using human exfoliated colonic epithelial cells

Abstract: The possibility of using exfoliated colonic epithelial cells for assessing the bioavailability of b-carotene was examined. Analysis of exfoliated colonic epithelial cells showed the presence of b-carotene and vitamin A. The b-carotene content was significantly lower in cells from stool samples of subjects on a b-carotene-poor diet than those receiving a single dose of a b-carotene supplement. Colonic epithelial cells isolated from stool samples collected daily during a wash-out period while the subjects were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…One-third to one-sixth of the enterocytes lining the intestine (approximately 10 10 cells) were shed daily into the stool in normal conditions. 159 Exfoliated enterocytes and colonocytes have been used to measure host response to dietary constituents, including nutrient uptake 160 and gene expression by polymerase chain reaction or gene microarray. [161][162][163][164] Gene expression in epithelial cells isolated from stool is modulated by disease 163,164 or dietary treatments, 160,161,164 suggesting that they provide a sensitive noninvasive marker for epithelial cell function.…”
Section: Future Opportunities and Needsmentioning
confidence: 99%
“…One-third to one-sixth of the enterocytes lining the intestine (approximately 10 10 cells) were shed daily into the stool in normal conditions. 159 Exfoliated enterocytes and colonocytes have been used to measure host response to dietary constituents, including nutrient uptake 160 and gene expression by polymerase chain reaction or gene microarray. [161][162][163][164] Gene expression in epithelial cells isolated from stool is modulated by disease 163,164 or dietary treatments, 160,161,164 suggesting that they provide a sensitive noninvasive marker for epithelial cell function.…”
Section: Future Opportunities and Needsmentioning
confidence: 99%
“…Many products such as carnitine (Kanter and Williamhe 1995), vitamin C (Goldfarb 1995), vitamin E (Goldfarb 1995;Beaton et al 2002), co-enzyme Q10 (Svensson et al 1999), zinc (Micheletti et al 2001), colecithin (Wu et al 2000), proanthocyanidin (Bagchi et al 2000), creatine (Powers et al 2004), polyphenols (Matuschek andSvanberg 2002), astaxanthin (Chien et al 2003), and beta-carotine (Gireesh et al 2004), etc. were shown to have signiWcant eVect on anti-oxidation.…”
Section: Introductionmentioning
confidence: 98%
“…Colonic epithelial cells were extracted and HPLC analysis was performed using a SPD 10A Shimadzu liquid chromatograph (Shimadzu, Kyoto, Japan) operating at room temperature as described previously (Gireesh et al 2004). A Whatman Partisil-5 ODS 3 column (Whatman Plc, Kent, UK) was used.…”
Section: Extraction Of B-carotene From Colonic Epithelial Cells and Hmentioning
confidence: 99%
“…Recently we have shown that exfoliated colonic epithelial cells isolated from stool samples of human subjects contain vitamin A and provitamin A carotenoids (Gireesh et al 2004). A direct relation between the dietary availability of carotenoids and the content of carotenoids in exfoliated colonic epithelial cells was found.…”
Section: Introductionmentioning
confidence: 98%